Effects of flanking loops on membrane insertion of transmembrane helices: a role for peptide conformational equilibrium - Gao, Jian; Chen, Jianhan (My University, 2013)
The ability of a transmembrane helix (TMH) to insert into a lipid bilayer has been mainly understood based on the total hydrophobicity of the peptide sequence. Recently, Hedin et al. investigated the influence of flanking loops on membrane insertion of a set of marginally hydrophobic TMHs using translocon-based membrane integration assays. While the flanking loops were found to facilitate the insertion in most cases, counter examples also emerged where the flanking loops hinder membrane insertion and contradict the hydrophobicity and charge distribution analyses. Here, coarse-grained free energy calculations and atomistic simulations were performed to investigate the energetics and conformational details of the membrane insertion of two representative marginally hydrophobic TMHs with (NhaL and EmrL) and without (NhaA and EmrD) the flanking loops. The simulations fail to directly recapitulate the contrasting effects of the flanking loops for these two TMHs, due to systematic overprediction of the stabilities of the transmembrane states that has also been consistently observed in previous studies. Nonetheless, detailed force decomposition and peptide conformation analyses suggest a novel mechanism on how the peptide conformational equilibrium in the aqueous phase may modulate the effects of flanking loops on membrane insertion. Specifically, the flanking loops in peptide EmrL interact strongly with the TMH segment and form stable compact conformations in the aqueous phase, which can hinder membrane absorption and insertion as these processes require extended conformations with minimal interactions between the flanking loops and TMH segment. This work also emphasizes the general importance of considering the peptide conformational equilibrium for understanding the mechanism and energetics of membrane insertion, an aspect that has not yet been sufficiently addressed in the literature.
Keywords: Coarse-grained; Molecular dynamics; PMF; Transmembrane helices; Hydrophobic scale